On power - Levin, Mark R. (Mark Reed), 1957- (Threshold Editions, an imprint of Simon & Schuster, LLC, 2025)
"Mark R. Levin delivers a profound analysis of the philosophy and structure of power and the critical impact of liberty on our collective future. Throughout history, from ancient civilizations to modern Western republics, power has been used to both oppress and liberate. To reward and exploit. To destroy and build. Monarchs, dictators, and elites who impose tyranny seek to consolidate power, stripping freedom from individuals to maintain control over societies. They use force and deception to ensure their rules remain unchallenged, claiming to act in the name of the common good while stripping individuals of their freedoms. In contrast, those who seek to use power for good--such as America's Constitutional Framers--understand that strong societies are born not from force, but consent. Societies built on checks and balances, fair elections, and the preservation of individual rights not only survive, but thrive. Following in the footsteps of works by thinkers such as Alexis de Tocqueville and Frédéric Bastiat, Mark R. Levin's On Power examines how power shapes history, offering invaluable insights into individual liberty, unalienable rights, and conservative principles from one of the leading philosophers of modern conservatism." --